MAKING OF STMIK JAKARTA Football Club (SJFC) HOMEPAGE USING NOTEPAD - Erwindi Firmansyah; Cut Asiana Gemawati SKom, MMS (Jurnal Sistem Informasi, 2005)
Information quickly when needed by the community was very good in the world of work and organizations and the public. One of the fast is the internet media.Therefore, the authors make this homepage to provide alternatives in finding all the information quickly and accurately about the organization STMIK Jakarta Football Club (SJFC). Further, the application is made by using notepad, because in creating and editing the homepage more easily without having to deal with the hassle of HTML programming language.